EXPLORATIONS DIVERSITY OF Dioscorea spp. VARIETIES FROM PASURUAN, EAST JAVA: INVENTORY AND CHARACTERIZATION - Fauziah Fauziah; S. Mas'udah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
Dioscorea spp. is the edible tubers from Dioscoreaceae family. Dioscorea is also an important crop which serves as a staple food and medicine. Discoreaceae exploration collecting mission had been conducted in 10 Districts of Pasuruan, East Java. Forty-four accessions were obtained during the exploration. It comprised of 5 species and 29 varieties i.e. 17 varieties of Dioscorea alata L., 8 varieties of Dioscorea his-pida Dennst., 2 varieties of Dioscorea esculenta (Lour.) Burkill., 1 variety of Dioscorea pentaphylla L. and 1 variety of Dioscorea bulbifera L. The results showed that morphological characteristic features of Dioscorea spp. tubers were broadly varied among species and even within varieties at the same species. Dioscorea spp. varieties ori-ginated from Pasuruan were mostly character-ized by its tuber shape, tuber flesh colour, outer and inner skin colour and tubers skin texture. Based on the interviews to local farmers, D. alata and D. hispida varieties were still widely grown because of its high tuber yields and its most acceptable taste than other Dioscorea species.